Immunomodulatory regulation by heat-labile enterotoxins and potential therapeutic applications. (3rd August 2021) - Knapp, Mary-Peyton A.; Johnson, Taylor A.; Ritter, Madison K.; Rainer, Robert O.; Fiester, Steven E.; Grier, Jennifer T.; Connell, Terry D.; Arce, Sergio
ABSTRACT: Introduction : Heat-labile enterotoxins (HLTs) and their cognate ganglioside receptors have been extensively studied because of their therapeutic potential. Gangliosides play arole in modulating effector cells of the immune system, and HLTs provide a novel means for stimulating ganglioside-mediated responses in immunocompetent cells. Areas covered : To evaluate the mechanisms of HLT adjuvanticity, a systemic literature review was performed using relevant keyword searches of the PubMed database, accessing literature published as recently as late 2020. Since HLTs bind to specific ganglioside receptors on immunocytes, they can act as regulators via stimulation or tapering of immune responses from associated signal transduction events. Binding of HLTs to gangliosides can increase proliferation of T-cells, increase cytokine release, augment mucosal/systemic antibody responses, and increase the effectiveness of antigen presenting cells. Subunit components also independently stimulate certain immune responses. Mutant forms of HLTs have potent immunomodulatory effects without the toxicity associated with holotoxins. Expert opinion : HLTs have been the subject of abundant research exploring their use as vaccine adjuvants, in the treatment of autoimmune conditions, in cancer therapy, and for weight loss, proving that these molecules are promising tools in the field of immunotherapy.